Applying The Principle “The Presumption Of Validity In Contracts And Conditions” In Enhancing Food Security For Newborns: An Integrative Jurisprudential And Medical Study - Abdullah Al-Qathami, Eman Mohammed (Journal of Neonatal Surgery, 2025)
This study highlights a fundamental Islamic legal maxim—“the presumption of validity in contracts and conditions”—and explores its contemporary applications in the field of food security and food supply systems for newborns. The research discusses health-related challenges associated with the safety and quality of infant foods and demonstrates how this principle can contribute to structuring food policies from an integrated legal and health perspective. Analytical, inductive, and descriptive methodologies were adopted, relying on classical jurisprudential sources and scientific evidence from reputable organizations such as the World Health Organization (WHO, 2021), the U.S. Food and Drug Administration (FDA, 2020), and the European Food Safety Authority (EFSA, 2022). The study concludes that this Islamic legal principle offers flexibility in regulating health-related conditions within contracts in ways that serve the interests of infants and prevent fraud or food-related harm.